Effect of high-fructose consumption in pregnancy on the bone growth of offspring rats - Li, Yijing; Liu, Xiaoqian; Chu, Yuning; Li, Cai; Gao, Tianlin; Jiang, Xiuli; Zhu, Zihan; Sheng, Qi; Han, Lei (Frontiers in Nutrition, 2023)
Growing evidence suggests that bone health is programmed in early life. Maternal diet may influence the skeletal development of offspring. We aimed to determine the possible effects of high-fructose intake during pregnancy on different aspects of long bone morphology in the offspring in rats and to initially explore the possible mechanisms. Pregnant Sprague‒Dawley rats were randomly divided into four groups and intragastrically administered the same dose of distilled water (CON, n = 12), 20 g/kg/d glucose (GLU, n = 12), 10 g/kg/d fructose (LFRU, n = 12) or 20 g/kg/d fructose (HFRU, n = 12) for 21 days during gestation. Computed tomography was used to analyze the cortical and cancellous bones of the distal femur of the offspring rats, and circulating bone metabolic biomarkers were measured by enzyme immunoassay. The results showed that high-fructose intake during pregnancy could decrease body weight, impair glucose metabolism, and increase serum leptin and uric acid in offspring. The offspring in the HFRU group had higher levels of N-terminal propeptide of type I procollagen (PINP) and C-telopeptide of type I collagen (CTX). The bone mean density (BMD), total cross-sectional area inside the periosteal envelope (Tt.Ar), cortical bone area (Ct.Ar), medullary (or marrow) area (Ma.Ar), and trabecular mean density of offspring in the HFRU group were lower than those in the CON group. Tartrate resistant acid phosphatase (Trap) staining showed that high-fructose intake during pregnancy could increase the number of osteoclasts and increase the absorption area. Our results suggested that excessive fructose intake during pregnancy could inhibit skeletal development in offspring. Thus, attention to fructose intake during pregnancy is important for bone development in offspring.